Hosea Stout : Lawman, Legislator, Mormon Defender - Prince, Stephen L. (Book collections on Project MUSE., 2016)
"Police chief, military officer, city attorney, legislator, and US Attorney, Hosea Stout influenced many of the major civil and political events of LDS and Utah history. He was accused in connection with several deaths and arrested on conspiracy charges in the murder of Richard Yates."--Provided by publisher